Is there always a Trade-off between Insurance and Incentives? The Case of Unemployment with Subsistence Constraints - Juliana Mesén Vargas; Bruno Van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2018)
This article analyzes the behavioral effects of unemployment benefits (UB) and it characterizes their optimal level when jobless people, who can carry out a subsistence activity, only survive if they have access to a minimum consumption level. Our model shows that if the level of UB is low enough, increasing its level or providing liquidity to the agent can decrease the duration in unemployment. Extensive numerical simulations indicate that the relationship between the level of the benefits and the probability of finding a formal job is frequently inverse U-shaped. We show that rewriting the insurance gain of the Baily-Chetty formula in terms of sufficient statistics requires specific modeling assumptions. The optimal replacement rate is generally higher than when subsistence is ignored.
Keywords: D91; H21; J64; J65; 330; liquidity effect; scarcity; monetary costs; optimal insurance